2006
DOI: 10.2320/matertrans.47.317
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgy and Kinetics of Liquid–Solid Interfacial Reaction during Lead-Free Soldering

Abstract: The wetting of a molten solder on metallic surfaces is a rather complex phenomenon. In addition to physical spreading due to surface tension reduction, there are interfacial metallurgical and flux chemical reactions with the metallic substrate surface. Substrate dissolution and intermetallic formation take place rapidly during soldering. Since lead-free soldering requires substantially higher soldering temperatures (around 250 C), the rates of intermetallic growth and substrate dissolution for lead-free solder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…k and k * are the growth kinetic constants of layer i depending on the operation mechanisms for the layer growth. These values are in agreement within about 20% with those obtained by Liang et al [27] for the Cu/liquid Sn-3.5 wt%Ag alloy and Cu/liquid Sn-3.5 wt%Ag-0.7 wt%Cu alloy couples at 225°C as well as with those obtained by extrapolation at 222°C of experimental results reported by Gagliano et al [11] for the Cu/liquid Sn couple for temperatures between 250 and 325°C. These values are in agreement within about 20% with those obtained by Onishi et al [18] and Paul et al [28] for the Cu/solid Sn couples at 220°C and 215°C, respectively.…”
Section: Resultssupporting
confidence: 92%
“…k and k * are the growth kinetic constants of layer i depending on the operation mechanisms for the layer growth. These values are in agreement within about 20% with those obtained by Liang et al [27] for the Cu/liquid Sn-3.5 wt%Ag alloy and Cu/liquid Sn-3.5 wt%Ag-0.7 wt%Cu alloy couples at 225°C as well as with those obtained by extrapolation at 222°C of experimental results reported by Gagliano et al [11] for the Cu/liquid Sn couple for temperatures between 250 and 325°C. These values are in agreement within about 20% with those obtained by Onishi et al [18] and Paul et al [28] for the Cu/solid Sn couples at 220°C and 215°C, respectively.…”
Section: Resultssupporting
confidence: 92%
“…The linear relationship between the reaction layer thickness and time -½ suggests that the growth is a diffusion-controlled process. Taking the overall thickness of the reaction product into consideration, the relationship can be expressed by [11,22] …”
Section: Resultsmentioning
confidence: 99%
“…It has been also reported, that rapid mechanical weakening of SnAgCu vs Cu joint occurs after aging at 100°C for 20 to 40 days. [11] Diffusion of Cu through Cu 3 Sn and Cu 6 Sn 5 layers leads to the formation of ''Kirkendall voids'' at the Cu/Cu 3 Sn and Cu 3 Sn/Cu 6 Sn 5 interfaces. Void fraction at the Cu/Cu 3 Sn interface increases after prolonged holding.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that additional alloying elements in the solder as well as the configuration of the metallization layer can significantly influence the growth kinetics and morphology of IMC formations. [4][5][6][7][8][9] A study on Ni-Sn IMC formations using Sn3.5Ag0.5Cu solder and electroless NiP layers at 523 K (250°C) revealed how the addition of P leads to the embrittlement of the solder joints, resulting in solder delamination and a significant decrease of the shear strength after only 180 min of reflow time. [10] Shen et al [7] investigated the IMC formation between Ni plates and Sn3.5Ag0.75Ni solders at 523 K and 553 K (250°C and 280°C) for reaction times of up to 10 hours and calculated an activation energy of 11 kJ/mol for Ni 3 Sn 4 formation.…”
Section: Introductionmentioning
confidence: 99%